PROFITABILITAS MEMEDIASI KECUKUPAN MODAL TERHADAP PERUBAHAN LABA PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2015-2019 - Bernhard Peter Nabut; Louis Ray Vincent Hutapea (Program Studi Magister Manajemen Universitas Advent Indonesia, 2021)
The profit earned by the company is important for management to anticipate potential bankruptcy. Therefore, changes in profit every year are always observed. This study was conducted to find out how Profitability mediates the Capital Test on Profit Changes in banking companies listed on the Indonesia Stock Exchange, in determining the sample, the sample is used with the aim of using criteria. The sample for this study is the 2015-2019 financial statements, with a total of 110 samples. Partially, Capital Adequacy and Profitability have a significant effect on Profit Changes. Likewise, simultaneously Capital Adequacy and Profitability have a significant effect on Profit Changes. Indirectly, Capital Adequacy affects Profit Changes mediated by profitability.